Interleukin-1 induces time-dependent potentiation in isolated rat islets: Possible involvement of phosphoinositide hydrolysis - Zawalich, W.S.; Dierolf, B.; Zawalich, K.C. (Endocrinology, 1989)
Prior exposure of isolated perifused rat islets to the monokine interleukin-1 (IL-1) amplifies their subsequent insulin secretory response to 10 mM glucose. This potentiating effect of the monokine is dose dependent, lasts for at least 45 min after IL-1 removal from the medium, and is not confined to glucose; IL-1 also potentiates the insulin secretory responses to tolbutamide and glyceraldehyde. IL-1 exposure of islets incubated with myo-[2â€ 3H]inositol to label their phosphoinositides (PI) results in an increase in [3H]inositol efflux, an event that persists long after removal of IL-1 from the medium. Direct measurements of labeled inositol phosphate accumulation substantiate the concept that this sustained [3H] inositol efflux response is the direct result of a sustained increase in PI hydrolysis. These results expand the list of compounds that induce time-dependent potentiation in islets to include IL-1. This action of the monokine, mediated at least in part by Pi-derived second messenger molecules, may contribute to its postulated effects on insulin and glucose homeostasis. © 1989 by The Endocrine Society.
Keywords: Animal; Hydrolysis; In Vitro; Inositol Phosphates; Insulin; Interleukin-1; Islets of Langerhans; Kinetics; Male; Phosphatidylinositols; Rats; Rats; Inbred Strains; Reference Values; Support; Non-U.S. Gov't; Time Factors; animal cell; controlled study; dept.nur; insulin; interleukin 1; male; nonhuman; pancreas islet; phosphatidylinositide; priority journal; radioisotope; rat; tolbutamide; ⚠️ Invalid DOI